Fluorescence-based reporter for gauging cyclic Di-GMP levels in Pseudomonas aeruginosa - Borlee, Bradley R. (2013)
The increased tolerance toward the host immune system and antibiotics displayed by biofilm-forming Pseudomonas aeruginosa and other bacteria in chronic infections such as cystic fibrosis bronchopneumonia is of major concern. Targeting of biofilm formation is believed to be a key aspect in the development of novel antipathogenic drugs that can augment the effect of classic antibiotics by decreasing antimicrobial tolerance. The second messenger cyclic di-GMP is a positive regulator of biofilm formation, and cyclic di-GMP signaling is now regarded as a potential target for the development of antipathogenic compounds. Here we describe the development of fluorescent monitors that can gauge the cellular level of cyclic di-GMP in P. aeruginosa. We have created cyclic di-GMP level reporters by transcriptionally fusing the cyclic di-GMP-responsive cdrA promoter to genes encoding green fluorescent protein. We show that the reporter constructs give a fluorescent readout of the intracellular level of cyclic di-GMP in P. aeruginosa strains with different levels of cyclic di-GMP. Furthermore, we show that the reporters are able to detect increased turnover of cyclic di-GMP mediated by treatment of P. aeruginosa with the phosphodiesterase inducer nitric oxide. Considering that biofilm formation is a necessity for the subsequent development of a chronic infection and therefore a pathogenicity trait, the reporters display a significant potential for use in the identification of novel antipathogenic compounds targeting cyclic di-GMP signaling, as well as for use in research aiming at understanding the biofilm biology of P. aeruginosa.